Epidemiology of cutaneous porphyria in Israel: a nationwide cohort study. (16th July 2019) - Edel, Y.; Mamet, R.; Snast, I.; Kaftory, R.; Mazor, S.; Hodak, E.; Lapidoth, M.; Elis, A.; Molad, Y.; Levi, A.
Abstract: Background: From a dermatologist's perspective, there are four major types of cutaneous porphyrias (CPs): porphyria cutanea tarda (PCT), erythropoietic protoporphyria (EPP), variegate porphyria (VP) and hereditary coproporphyria (HCP). Scarce data are available regarding the epidemiology of CPs. Objectives: To describe the epidemiology of CPs in Israel, including distribution, incidence and prevalence rates of major types. Methods: This retrospective study includes all patients who were diagnosed with CPs between the years 1988–2018. It is based on data from Israel's National Service for the Biochemical Diagnoses of Porphyrias, and Israeli patients' nationwide electronic medical charts. Incidence and prevalence rates were calculated. Results: Of 173 patients with CPs diagnosed during a 30‐year period, 65 (38%) had VP, 62 (36%) had PCT, 31 (18%) had HCP and 15 (9%) had EPP; with incidence rates of 0.29, 0.30, 0.17, 0.07, and prevalence rates of 6.3, 4.8, 2.9, 1.6, respectively, per million population. Characteristics of patients with PCT differed from those with other CPs with regard to lack of family history, older mean age at diagnosis [51 vs. 36 (VP), 35 (HCP) and 25 (EPP) years] and male predominance (81% vs. similar distribution). All patients with PCT were diagnosed at adulthood, while 20%, 19% and 15% of patients with VP, HCP and EPP, respectively, were diagnosed during childhood or adolescence. Conclusions: Variegate porphyria and PCT were found to be the most prevalent in Israel; however, CPs might be underdiagnosed, thus dermatologists' awareness of these rare disorders is highly important.